Investigating the influence of emitted Cadmium from crude oil combustion on glutathione level in workers at Al- Qudis power plant, Baghdad - B. Mahmood, Mahmood; Y. Yaseen, Nahi; S. Al-Zubaidi, Fawzi (Iraqi Journal of Science, 2025)
Al-Qudis power plant was chosen, as one of the power stations of Baghdad, to investigate the effects of Cadmium that emitted from combustion of crude oil in that power plant on the workers’ glutathione serum level. Air samples were taken seasonally during August 2011- July 2012 from four sites at Al- Qudis power plant which are oil treatment unit 1(site 1), oil treatment 2 (site2), pre –chimney 1(site 3) and pre-chimney 2 (site 4), to measure levels of heavy metal (cadmium) under study. Blood samples were collected from the workers to estimate the heavy metal Cadmium. Air cadmium levels during summer (August and September) were varied from 6.26 ± 0.6 μg/m3 at site 1 to 6.89 ± 0.67 μg/m3 at site 3, while in spring (end of March, and end of April); these figures were ranged from 4.95 ± 0.39 μg/m3 at site 4 to 6.08 ± 0.5 μg/m3 at site 2. However, autumn (end of October and November) had mean values lied between 4.89 ± 0.6 μg/m3 at site 3 and 5.7 ± 0.57 μg/m3 at site 2. Winter (end of December 2011,January and February 2012)data gave a range of 4.51 ± 0.46 μg/m3 at site 4 and 4.98 ± 0.57 μg/m3 at site 3. The current results exceeded the acceptable levels of Cd for WHO which is around 0.3 μg/m3. The results of current study showedthatthe mean value ofcadmiumin the blood of occupational sampleswas6.418 ± 0.636 μg/l which was significantly higher than those of (P≤ 0.05) environmental (5.247 ± 0.418 μg/l) and (P≤ 0.01) control (1.854±0.41 μg/l) samples.For reduced Glutathione (GSH) concentration, the current study results showed the highest value 5.4 ± 0.52 μmol/l in respect to control sample, while the lowest data 2.2595 ± 0.412 μmol/l and 2.6625 ± 0.475 μmol/l have been found in environmental and occupational samples, respectively.These results indicate that heavy metal (cadmium) influence GSH level of Al-Qudis’s workers.